Features of Ocular Blood Flow and Methods for Its Study - N. Yu. Yusef; E. E. Kazaryan; A. A. Rafaelyan; S. A. Shashorina (Oftalʹmologiâ, 2023)
The review presents information about the basic knowledge about the regulation of blood flow in the retina, based on data obtained in animal experiments using invasive methods. Along with the well-known instrumental methods for diagnosing vascular pathology of the eye, new high-tech methods for studying the microcirculation of the eye are used, which make it possible to most reliably assess the degree of circulatory disorders in the vessels of the eyeball. Thanks to the development of non-invasive ultrasound research methods, it became possible to study in more detail the state of blood flow in the vessels of the eyeball in people with vascular pathology of the eye. An important feature of the eye hemodynamics is its dependence on intraocular pressure and the presence of self-regulation of blood flow in the retina, including changes in the illumination of the retina, blood pressure, and so on. The blood supply to the eye can also be affected by pharmacological agents that are commonly used in the treatment of systemic diseases.